A cognitive semantic analysis of locative and spatial constructions in Bangla - Ghosh S. (My University, 2025)
This paper examines certain spatial constructions in Bangla by identifying and describing locative and spatial postpositions used in different spatial constructions. The initial data are based on the Topological Relation Picture Series (TRPS) description. This is an exploratory study for Bangla locative and spatial postpositions in a cognitive semantics framework. For describing location, Bangla uses two main types of construction: first, Trajector-Landmark + Locative marker-copula and, second, Trajector-Landmark + GEN-Postposition-Verb-Copula. Bangla is observed to have 14 spatial postpositions for the TRPS picture description. These are derived from spatial nouns and are marked with locative case. The paper shows that apart from postpositions and locative markers, the copula verb also plays an important role in the cognition of space in Bangla. © 2021 Walter de Gruyter GmbH, Berlin/Boston. All rights reserved.